Wednesday
March 29, 2017

Post a New Question

Posted by on .

simplify
z-(2z-[3z-(4z-5z)-6z0-7z]-8z

  • algebra - ,

    Check for a typo:
    I will assume that -6z0 is supposed to be -6z
    You also have one ( bracket which is not closed, I will assume it closes after the -8z .

    z-(2z-[3z-(4z-5z)-6z-7z]-8z)
    = z-(2z-[3z-4z+5z-6z-7z]-8z)
    = z - (2z -[-9z] -8z)
    = z - (2z+9z-8z)
    = z - (3z)
    = -2z

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question